The placebo effect and its determinants in fibromyalgia: a systematic review and meta-analysis of randomised controlled trials - Chen, Xi (2015)
Introduction: Placebo has been proven effective in many diseases but whether it is effective in the treatment of fibromyalgia, a chronic widespread pain condition affecting 2% of general population, is unknown.